PERSEPSI SISWA TENTANG PENERAPAN CASE BASED LEARNING (CBL) PADA MATA PELAJARAN GEOGRAFI DI SMA PEMBANGUNAN LABORATORIUM UNP - Alfahri, Muhammad; Nofrion, Nofrion (JURNAL BUANA, 2023)
This study aims to determine students' perceptions of the application of case based learning (CBL) in Geography at the UNP Laboratory Development High School. This type of research is descriptive with a qualitative approach. The object of research is the opinion of students with research subjects namely students and teacher of class XII IIS. Data collection techniques in the form of observation, interviews and documentation. The results of the study describe that students have a positive perception of the application of case based learning (CBL) because it is able to improve students' abilities such as critical thinking skills, communication skills, collaboration skills, participation skills and student involvement in learning. So that case based learning (CBL) can be used by teachers as an alternative method in learning.